6 - 6x = -2(x + 5)
6 - 6x = -2x - 10
6 = 4x - 10
16 = 4x
6-6x=2(x+5)
(6-6x)/2 = x+5
3-3x=x+5
3-5=4x
-2=4x
x= -2/4
x= -1/2
x= -0.5
Answer:
x=5
Step-by-step explanation:
3x+11=10x-12
We move all terms to the left:
3x+11-(10x-12)=0
We get rid of parentheses
3x-10x+12+11=0
We add all the numbers together, and all the variables
-7x+23=0
We move all terms containing x to the left, all other terms to the right
-7x=-23
x=-23/-7
x=3+2/7
The equation of the vertical asymptote for the graph of y = 1/x - 2 is x = 2.
A vertical asymptote occurs when the denominator of a rational function (a function that can be written as the ratio of two polynomials) equals zero, but the numerator does not.
The equation is given in the question, as follows:
y = 1/x−2
We have to determine the vertical asymptote for the graph
In this case, the denominator is x, and when x = 2, the denominator equals zero.
However, since the numerator does not equal zero at x = 2, the graph will approach, but never touch the x-axis at that point, which creates a vertical asymptote.
Thus, the equation of the vertical asymptote for the graph of y = 1/x - 2 is x = 2.
Learn more about the vertical asymptote here:
#SPJ2